My fair lady - Lerner, Alan Jay, 1918-1986.; Loewe, Frederick, 1901-1988.; Cukor, George, 1899-1983.; Hepburn, Audrey, 1929-1993.; Harrison, Rex.; Holloway, Stanley; Hyde-White, Wilfrid; Cooper, Gladys, 1888-1971.; Brett, Jeremy, 1933-1995.; Bikel, Theodore; Shaw, Bernard, 1856-1950.; Warner Bros. Pictures (1923-1967); et al. (Burbank, CA : Warner Home Video, 1998)
A Cockney waif is transformed by a linguistics professor into an elegant lady.
Based on the play: Pygmalion / by George Bernard Shaw; and the musical play by Alan Jay Lerner and Frederick Loewe.
Originally produced as motion picture in 1964.
Restored from its original version in 1994.
Special features: Feature-length audio commentary that includes art director Gene Allen, singer Marni Nixon and restorers Robert A. Harris and James C. Katz; behind-the-scenes documentary 'The fairest fair lady'; alternate Audrey Hepburn vocal versions of 'Show me' and 'Wouldn't it be loverly'; interactive menus; production notes; 4 theatrical trailers; scene access.
Closed-captioned for the hearing impaired.
Director of photography, Harry Stradling; editor, William Ziegler.
Keywords: Man-woman relationships -- England -- London -- Drama; Speech and social status -- England -- London -- Drama; Musical films; Feature films; Video recordings for the hearing impaired